The Lasioseius phytoseioides species group (Acari: Blattisociidae): new characterisation, description of a new species, complementary notes on seven described species and a taxonomic key for the group - de Moraes, Gilberto J.; Abo-Shnaf, Reham I.a.; Pérez-Madruga, Yanebis; Sánchez, Leocadia; Karmakar, Krishna; Ho, Chyi-Chen (Zootaxa, 2015)
The Lasioseius phytoseioides species group was first characterised over 50 years ago. Two species of this group, Lasioseius chaudhrii (Wu & Wang) and Lasioseius parberlesei Bhattacharyya, have been considered potentially effective as biological control agents of pest mites of the family Tarsonemidae on rice (Oryza sativa L.) in Asia. A new characterisation of the species group is presented, taking into account a new species here described, Lasioseius piracicabensis Moraes & Pérez-Madruga n. sp., as well as other species mostly described since the first characterisation of the group. The main characteristics of the included species are the reduced number of dorsal idiosomal setae, including the absence of j1 and z1; antiaxial surface of fixed cheliceral digit with a subterminal pointed process; and males with broad lateral expansion of the peritrematic shield in the region between coxae II–III, bearing a pore and a lyrifissure. Complementary notes are presented for Lasioseius annandalei Bhattacharyya & Bhattacharyya, Lasioseius chaudhrii (Wu & Wang), Lasioseius parberlesei Bhattacharyya, L. phytoseioides Chant, Lasioseius punjabensis Bhattacharyya & Sanyal, Lasioseius terrestris Menon & Ghai and Lasioseius youcefi Athias-Henriot. New synonymies are proposed and possible misidentifications in the literature are discussed. A dichotomous key is presented to help the identification of the species of the group, and the distribution of the species is summarised.